FUNDAMENTALS OF MODERN APPROACH TO TEACHING UZBEK NATIONAL MUSICAL ART - Turdiyev Shavkat Akhmedovich (Journals Park Publishing, 2024)
This scientific article analyzes the foundations of modern approaches to the teaching of Uzbek national musical art. The article examines the importance of active teaching methods, modern technologies and individual approaches in the educational process. Information is provided about the activities carried out in order to introduce new pedagogical approaches to teaching the rich heritage of Uzbek national musical art, to develop student creativity and preserve cultural heritage. The article contains important recommendations to make the process of teaching Uzbek national music more effective and interesting.
Keywords: Uzbek national music arts, educational process, modern approaches, active teaching methods, technology application, Individual approach, practical classes, music festivals, creative development of students, cultural heritage, Multimedia materials, online education, music education, pedagogical approaches, mutual exchange of experience.